2011
DOI: 10.2319/051010-252.1
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial growth of Class III subjects six to sixteen years of age

Abstract: Objective: To characterize the mixed-longitudinal craniofacial growth of untreated, white, Class III subjects 6 to 16 years of age. Materials and Methods: Serial cephalograms of 19 females and 23 males with Class III malocclusion were evaluated at three time points (6-8, 10-12, and 14-16 years of age). A similar number of Class I controls were randomly selected and matched for age and sex. The cephalograms were traced and digitized, and 20 variables were evaluated. Growth patterns were quantified, and class an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
2
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 19 publications
7
42
2
4
Order By: Relevance
“…By the end of the treatment, the majority of patients maintained their initial vertical growth pattern, showing some changes in growth direction, mainly in those with neutral rotation. Of the former, some patients shifted toward having clockwise growth direction, whereas others had counterclockwise growth direction; suggesting that in response to therapy, changes toward clockwise mandibular rotations should not always be expected, as previously reported by others (Kiliçoglu & Kirliç, ; Nevzatoğlu & Küçükkeleş, ; Wolfe et al, ).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…By the end of the treatment, the majority of patients maintained their initial vertical growth pattern, showing some changes in growth direction, mainly in those with neutral rotation. Of the former, some patients shifted toward having clockwise growth direction, whereas others had counterclockwise growth direction; suggesting that in response to therapy, changes toward clockwise mandibular rotations should not always be expected, as previously reported by others (Kiliçoglu & Kirliç, ; Nevzatoğlu & Küçükkeleş, ; Wolfe et al, ).…”
Section: Discussionsupporting
confidence: 64%
“…This type of skeletal relationship represents one of the most challenging issues faced by the orthodontic clinician due to the unpredictable and potentially unfavorable vertical growth pattern that these patients may exhibit (Kim, Viana, Graber, Omerza, & BeGole, ; Zhang et al, ). Wolfe et al reported that, compared with a Class I control group, patients with Class III malocclusion display hyperdivergent jaws and increased inferior facial height (Wolfe, Araujo, Behrents, & Buschang, ). Treatment has been aimed at maxillary advancement and/or control of jaw growth, and several devices have been designed for this purpose such as protraction face masks (FMs), chincups, mandibular cervical hedgear, and functional orthopedic appliances (Baccetti, Rey, Angel, Oberti, & McNamara, ; Baccetti, Rey, Oberti, Stahl, & McNamara, ; Baik, Jee, Lee, & Oh, ; Rey, Angel, Oberti, & Baccetti, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…22 The linear distances and angular measurement that expressed the vertical dimension of MS and the area of MS were largest in the Class III group compared to the Class I and Class II groups. Several studies [22][23][24] reported a larger mandible in the Class III relationship, including its symphysis, than in the other AP relationships.…”
Section: Discussionmentioning
confidence: 99%
“…5 Clearly, children and adolescents with Class III malocclusion do not have a typical skeletal phenotype. 8,9 This growth can also occur late in adolescence or even in early adulthood, particularly in relation to mandibular prognathism. Unlike Class II malocclusions, which tend to improve skeletally with growth, a Class III malocclusion if allowed to develop will become worse with age, with the growth of the mandible exceeding the growth of the maxilla.…”
Section: Aetiology Of Class III Malocclusionmentioning
confidence: 99%